Evaluation of massive education in prison health: a perspective of health care for the person deprived of freedom in Brazil - Valentim, Janaína L. R. S.; Dias-Trindade, Sara; Oliveira, Eloiza S. G.; Romão, Manoel H.; Fernandes, Felipe; Caitano, Alexandre R.; Bonfim, Marilyn A. A.; Dias, Aline P.; Gusmão, Cristine M. G.; Morais, Philippi S. G.; Melo, Ronaldo S.; Fontoura de Souza, Gustavo; et al. (Frontiers in Public Health, 2023)
Education, with an emphasis on prison health, has acted as a policy inducing changes in work processes, which the Brazilian National Health System (SUS) has used, and which is present in permanent health education, which promotes health care for people deprived of liberty. This article aims to present an analysis of the impacts of the strategy of massive education on prison health in Brazil from the perspective of health professionals and other actors operating in the Brazilian prison system. The data used in the study come from a questionnaire consisting of 37 questions applied nationwide between March and June 2022. Responses were collected from students who completed the course “Health Care for People Deprived of Freedom” of the learning pathway “Prison System”, available in the Virtual Learning Environment of the Brazilian Health System (AVASUS). This course was offered nationally, whose adhesion (enrollment) occurred spontaneously, i.e., the course was not a mandatory. The data collected allowed us to analyze the impacts of massive education on prison health. The study also shows that the search for the course is made by several areas of knowledge, with a higher incidence in the health area, but also in other areas, such as humanities, which also work directly with the guarantee of the rights of people deprived of liberty, which are professionals in the areas of social work, psychology, and education. The analysis based on the data suggests that the massive education mediated by technology through the courses of the learning pathway, besides disseminating knowledge–following the action plan of the 2030 Agenda of the United Nations Educational, Scientific and Cultural Organization (UNESCO)–, are an effective tool to promote resilience in response to prison health and care demands of people deprived of liberty.